The level of knowledge of elderly people about halitosis due to wearing a complete denture at Lubuk Buaya Health Centre: Tingkat pengetahuan manula tentang halitosis akibat pemakaian gigi tiruan lengkap di Puskesmas Lubuk Buaya - Aulia Zarvi; Resa Ferdina; Kornialia (Makassar Dental Journal PDGI Makassar, 2023)
Tooth loss in the elderly can affect physical conditions such as aesthetics, speech comfort, mastication system, and a decrease in the vertical dimension of the face; so prosthodontic treatment is needed using a denture. Halitosis in complete denture users oc-curs due to a wide denture base which can cause reduced saliva production. The purpose of this study was to determine the le-vel of knowledge of seniors about halitosis due to the use of GTL at Lubuk Buaya Health Centre. Quantitative research with descriptive type and cross-sectional design. The population was elderly patients who used GTL at Puskesmas Lubuk Buaya as many as 40 samples using total sampling technique. The research was conducted using a questionnaire in the form of a sheet of paper. The results of the study showed that the most knowledge was good, namely 37 people (92.5%) about halitosis due to the use of GTL at Lubuk Buaya Health Centre. It was concluded that the elderly GTL users at Puskesmas Lubuk Buaya mostly had good knowledge about halitosis.